2008
DOI: 10.1016/j.jasms.2008.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Surface-induced dissociation shows potential to be more informative than collision-induced dissociation for structural studies of large systems

Abstract: The ability to preserve noncovalent, macromolecular assemblies intact in the gas phase has paved the way for mass spectrometry to characterize ions of increasing size and become a powerful tool in the field of structural biology. Tandem mass spectrometry experiments have the potential to expand the capabilities of this technique through the gas-phase dissociation of macromolecular complexes, but collisions with small gas atoms currently provide very limited fragmentation. One alternative for dissociating large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
103
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 71 publications
5
103
0
Order By: Relevance
“…Black-body infrared radiative dissociation [15], electron-capture dissociation [17], infrared multiphoton dissociation [14,16], and surface-induced dissociation [18,64] have all been applied to protein assemblies. Of these, the latter is notable for the large amount of energy deposited into the protein complexes in a very short time, resulting in more extensive dissociation than that in CID [65]. Furthermore, small multimeric complexes were shown to dissociate into equally charged monomeric parts, rather than monomers and stripped oligomers [64,65].…”
Section: Frontiers In Gas-phase Activation Of Protein Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…Black-body infrared radiative dissociation [15], electron-capture dissociation [17], infrared multiphoton dissociation [14,16], and surface-induced dissociation [18,64] have all been applied to protein assemblies. Of these, the latter is notable for the large amount of energy deposited into the protein complexes in a very short time, resulting in more extensive dissociation than that in CID [65]. Furthermore, small multimeric complexes were shown to dissociate into equally charged monomeric parts, rather than monomers and stripped oligomers [64,65].…”
Section: Frontiers In Gas-phase Activation Of Protein Complexesmentioning
confidence: 99%
“…Of these, the latter is notable for the large amount of energy deposited into the protein complexes in a very short time, resulting in more extensive dissociation than that in CID [65]. Furthermore, small multimeric complexes were shown to dissociate into equally charged monomeric parts, rather than monomers and stripped oligomers [64,65]. These differences are rationalized in terms of the collisions being more energetic in the center-of-mass frame and the speed of energy deposition being far greater [65].…”
Section: Frontiers In Gas-phase Activation Of Protein Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…8B, bottom panel), corresponding to the removal of close to the complete C-terminal ϳ10-kDa domain. Such fragmentation of the polypeptide backbone during collisional activation of proteins in the gas phase is unusual, and it is indicative of a particularly labile covalent bond (55). Formation of AtCpn20 mut ⌬C was not observed with free AtCpn20 mut (data not shown) but only in the presence of the chaperonin, suggesting that one domain of an AtCpn20 mut subunit is excluded from interacting with AtCpn60␣ 7 ␤ 7 and is forced to adopt an alternative conformation, thereby rendering it susceptible to fragmentation in the MS measurement.…”
mentioning
confidence: 99%
“…With surfaces, the collisional cross-section is significantly greater than for comparatively smaller gas ions, thereby allowing for superior energy transfer [157]. In the context of intact protein analyses, SID has been demonstrated to allow for superior fragmentation of larger species than ECD/ETD [161]. Especially in the context of native protein analysis, applications with SID have demonstrated that individual subunits of a multiprotein complex can be dislodged without subsequent unfolding of the dissociated monomer, as seen with CID/HCD [161].…”
Section: Techniques For the Fragmentation Of Intact Proteinsmentioning
confidence: 99%